DAMPAK EKONOMI TUMPAHAN MINYAK DI TELUK BALIKPAPAN PADA PEMANFAATAN EKOSISTEM MANGROVE DI JENEBORA PENAJAM PASER UTARA - Nurul Ovia Oktawati; Anisa Nur Fadilah; Qoriah Saleha (EnviroScienteae, 2022)
Jenebora was one of the areas directly affected by the oil spill in the waters of Balikpapan Bay in 2018. It is estimated that almost 80% of the mangroves in the area were damaged. Oil spills into the sea have the potential to have a negative impact on the survival of the flora and fauna in it. This study aimed to measure the economic impact of the oil spill in Balikpapan Bay on the utilization and management of mangrove resources in Jenebora Village, Penajam Paser Utara. Economic valuation is a form of analytical approach used to assess the economic impact of mangrove damage. The results showed that the damage caused by the oil spill on the mangrove ecosystem was estimated a Rp. 41,082,027,068/year or Rp. 2,334,206,083ha/year. This value is estimated from the loss of fish resources that have economic value, as well as the damage to the function of the mangrove ecosystem as archery abrasion, reducing pollution and producing carbon. The policy recommendations in this study are the need for actions and rules related to the management and control of marine pollution that are integrated with other regulations, the need for Pertamina to improve equipment maintenance and immediately carry out post-event environmental restoration and ensure the allocation of fishing areas for traditional fishermen and continuous assistance to environmental recovery.